2022
DOI: 10.1111/sltb.12856
|View full text |Cite
|
Sign up to set email alerts
|

Application of minority stress and the interpersonal theory of suicide in bisexual+ versus gay/lesbian young adults

Abstract: Introduction Sexual minority young adults are at increased risk for suicidal ideation (SI) compared with heterosexual young adults. Though several frameworks exist to explain the development of suicide risk, including the Interpersonal Theory of Suicide (IPTS) and the Minority Stress Model, few studies have examined these frameworks simultaneously. This study examines these frameworks longitudinally among sexual minority young adults. Methods A total of 792 sexual minority young adults (50% bisexual+, 50% gay/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 83 publications
7
23
1
Order By: Relevance
“…However, it is difficult to compare these findings to prior studies because of differences in the ages of participants (Chang et al, 2021) and the operationalization of race/ethnicity (Pate & Anestis, 2020). Finally, we did not find differences between gay/lesbian and bi+ participants, which is consistent with some prior studies (Chang et al, 2021, 2022), but not others (Silva et al, 2015; Wolford-Clevenger et al, 2020). Although the current findings do not resolve the mixed evidence, they still suggest that group differences found in prior studies are unlikely to be due to differences in psychometric properties of the INQ-15.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, it is difficult to compare these findings to prior studies because of differences in the ages of participants (Chang et al, 2021) and the operationalization of race/ethnicity (Pate & Anestis, 2020). Finally, we did not find differences between gay/lesbian and bi+ participants, which is consistent with some prior studies (Chang et al, 2021, 2022), but not others (Silva et al, 2015; Wolford-Clevenger et al, 2020). Although the current findings do not resolve the mixed evidence, they still suggest that group differences found in prior studies are unlikely to be due to differences in psychometric properties of the INQ-15.…”
Section: Discussionsupporting
confidence: 93%
“…We used baseline data from a longitudinal study of risk factors for suicidal thoughts and behaviors among sexual minority young adults (Chang et al, 2022). Participants were recruited in 2020 through Prolific, and required to meet the following criteria: (a) 18–29 years old; (b) identify as gay, lesbian, or bisexual; (c) live in the U.S.; and (d) be able to read English.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisexual people often experience discrimination, rejection, and prejudice from both heterosexual and gay/lesbian individuals, resulting in an experience termed "double discrimination" (Doan Feinstein & Dyar, 2017). Preliminary research provides support for the association between bisexualspecific discrimination and greater risk for suicidal thoughts and behaviors (Chang et al, 2022;Mereish et al, 2017a), as well as potential mechanisms underlying these associations (e.g., perceived burdensomeness, Chang et al, 2022;loneliness, Mereish et al, 2017b). In our prior work, we found that antibisexual discrimination at baseline was associated with suicidal ideation 2 months later, but the association became nonsignificant after accounting for suicidal ideation at baseline (Chang et al, 2022).…”
mentioning
confidence: 91%
“…In sum, prior research has demonstrated that antibisexual discrimination is associated with suicidal ideation, but no prior studies have examined aspects of positive identity or dispositional resilience as buffers of these associations. Therefore, building on our prior work focused on the main effects of antibisexual discrimination on suicidal ideation (Chang et al, 2022), the present study examined whether aspects of positive identity (community, authenticity, and intimacy) and dispositional resilience buffered the longitudinal associations between antibisexual discrimination and suicidal ideation 1 and 2 months later. We hypothesized that higher levels of each positive identity factor would buffer the associations between antibisexual discrimination and suicidal ideation at 1- and 2-month follow-up, such that the associations would be weaker at higher levels of each positive identity factor.…”
mentioning
confidence: 99%